2021
DOI: 10.3390/jcm10214890
|View full text |Cite
|
Sign up to set email alerts
|

Do Not Miss the (Genetic) Diagnosis of Gaucher Syndrome: A Narrative Review on Diagnostic Clues and Management in Severe Prenatal and Perinatal-Lethal Sporadic Cases

Abstract: With a growing number of proved therapies and clinical trials for many lysosomal storage disorders (LSDs), a lot of hope for many patients and families exists. However, there are sometimes cases with poor prognosis, fatal outcomes when our efforts must be directed towards a prompt and correct genetic diagnosis, which offers the only possibility of providing the family with appropriate prevention and treatment. To address this issue, in this article, we present the clinical and genetic hallmarks of the lethal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…GD type 2 (# 230900) has been termed as acutely neuronopathic because of progressive neurodegeneration, while GD type 3 (# 231000), a subacute neuronopathic form, has a later onset of CNS signs and a highly variable rate of progression. Opisthotonus, bulbar signs (swallowing disorders), oculomotor paralysis (or bilateral fixed strabismus), and hepatosplenomegaly in the first 3–6 months of a patient’s life are very suggestive of GD type 2 [ 19 ]. GD3 patients usually present with similar somatic signs and symptoms to those observed in GD1 [ 20 , 21 ].…”
Section: The Liver and Gaucher Disease Acid Sphingomyelinase Deficien...mentioning
confidence: 99%
“…GD type 2 (# 230900) has been termed as acutely neuronopathic because of progressive neurodegeneration, while GD type 3 (# 231000), a subacute neuronopathic form, has a later onset of CNS signs and a highly variable rate of progression. Opisthotonus, bulbar signs (swallowing disorders), oculomotor paralysis (or bilateral fixed strabismus), and hepatosplenomegaly in the first 3–6 months of a patient’s life are very suggestive of GD type 2 [ 19 ]. GD3 patients usually present with similar somatic signs and symptoms to those observed in GD1 [ 20 , 21 ].…”
Section: The Liver and Gaucher Disease Acid Sphingomyelinase Deficien...mentioning
confidence: 99%
“…24,26,28,33 In others, these were histological findings (GBA, IMPAD1, and EPG5) or dissection findings (cerebral hemisphere fusion in POMT1, CENPJ, and NBN), which are often not available in postnatal cohorts. 20,21,23,32,[35][36][37] In certain instances, these unusual findings appear to be consequences of a more severe genotype, for example, nonsense CDK8 variant presenting with lethality, biallelic variants in dominant disorder genes presenting with severe manifestations (ENG) or digenic inheritance with blended phenotype (FBN1&FBN2 variant co-inheritance). Genotype-phenotype studies in other genetic diseases have revealed similar correlations of complex phenotypes with severe genotypes.…”
Section: T a B L E 1 Cases With Variants In Same Molecular Pathways O...mentioning
confidence: 99%